Aging in rare intellectual disability syndromes. Issue 1 (16th August 2013) - Dykens, Elisabeth M.; Silverman, Wayne; Mailick, Marsha R.
<x xml:space="preserve">Abstract</x> This review highlights several methodological challenges involved in research on aging, health, and mortality in adults with rare intellectual disability syndromes. Few studies have been performed in this area, with research obstacles that include: the ascertainment of older adults with genetic versus clinical diagnoses; likelihood that adults will not receive adequate health care and referrals to genetic specialists; cohort differences related to generational and treatment effects; and increased mortality and selective survival biases. Even so, aging in Prader‐Willi and Williams syndromes are reviewed as they reveal new insights into the phenotypic expression and treatment options for older adults with these disorders. The review ends with recommendations for future research that takes better advantage of genetic advances, changes in adult phenotypes, and ties across syndrome‐specific research silos. Although aging in rare neurodevelopmental disorders is barely on the research landscape, the field stands to learn much from these older adults. © 2013 Wiley Periodicals, Inc. Dev Disabil Res Rev 2013;18:75–83.